Penerapan Data Mining Dalam Proses Hukum Pidana Bagi Pelaku Kekerasan Pada Wanita Menggunakan Algoritma C4.5 - Simanjuntak, Lidya Priscila (ADA Journal of Information System Research, 2024)
Violence against women is an act that results in physical, sexual or psychological harm or suffering to women, including threats of certain actions, coercion or arbitrary deprivation of liberty, whether occurring in public or in private life. The problems that have occurred to the POLDASU in handling the criminal legal process for violence against women are handled by the Head of the PPA 1 (Women and Children Protection) by collecting the identity of the perpetrator of violence, the identity of the victim, and the identity of the witness, evidence, and scene design according to the facts. the cause of the violence, as well as the handling of the autopsy and post-mortem that will be applied. So far, the Head of the PPA 1 (Women and Children Protection) has to conduct an in-depth investigation of the data related to the occurrence of violence against women and it takes a long time, so that the criminal legal process that will be imposed must also be adjusted to the violence that occurs against women. Thus, the application of data mining in the criminal law process against perpetrators of violence against women is very necessary to assist the Kanit PPA 1 (Women and Children Protection) in adjusting the types of acts of violence against women against the criminal law that will be given. The author uses the C4.5 algorithm in the application of data on criminal law processes with violence that occurs against women.